Implementasi Pengawasan Bawaslu dalam Pelaksanaan Pemilu 2024 di Provinsi Banten - Pahlevi, Reza Syah; Nurikah; Rayhan, Ahmad (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study highlights the importance of election supervision from a political and administrative law perspective to prevent delegitimization of the election process and results, and to anticipate violations in an integrated manner. The focus of the study is the supervision carried out by the Banten Province Bawaslu on findings and reports of violations in the 2024 pre-election, based on Bawaslu Regulation Number 7 of 2022. This study uses Supervision Theory and Law Enforcement Theory, with qualitative methods and an empirical legal approach. The results of the study show that Bawaslu has carried out supervision of the 2024 election, despite facing obstacles, such as the limited number of supervisors, the short time to handle violations, and the limited quality of human resources. Based on Article 92 of Law Number 7 of 2017, the number of Bawaslu members at each level is still minimal, with only 5 to 7 people at the provincial level. Administrative violations dominate with 8 cases, such as the installation of campaign equipment in prohibited places, the use of government facilities, places of worship, and government offices for campaigns. In addition, 2 cases of criminal violations in the form of money politics, 5 cases of violations of the code of ethics, and 7 other violations of the law were found. In conclusion, despite implementing Perbawaslu Number 7 of 2022, the Banten Province Bawaslu still faces various obstacles. This study recommends increasing the role of institutions, harmonizing regulations between the KPU and Bawaslu, and adding human resources to strengthen supervision of election violations.